Asarum chueyi (Aristolochiaceae), a new species from the foothills of the Blue Ridge Mountains of Tennessee and Virginia, USA - Sinn, Brandon T. (Phytotaxa, 2015)
The forests of eastern North America continue to yield new species, despite more than 200 years of botanical exploration. As a result of fieldwork conducted from 2012–2014, a new Asarum (Aristolochiaceae) species was found in the foothills of the Blue Ridge Mountains of Tennessee and Virginia. This species, A. chueyi, is here distinguished from other North American Asarum species by a unique combination of several morphological characters (calyx tube shape, style extension length, abaxial sepal reticulation, and stamen morphology). Furthermore, a taxonomic key to the species of Blomquist’s informal Virginica group, along with a new combination for Hexastylis sorriei Gaddy, which has not been validly published in Asarum, is provided.